Graphite as Cointercalation Electrode for Sodium‐Ion Batteries: Electrode Dynamics and the Missing Solid Electrolyte Interphase (SEI). Issue 16 (22nd February 2018) - Goktas, Mustafa; Bolli, Christoph; Berg, Erik J.; Novák, Petr; Pollok, Kilian; Langenhorst, Falko; Roeder, Maximilian v.; Lenchuk, Olena; Mollenhauer, Doreen; Adelhelm, Philipp
Abstract: The intercalation of solvated sodium ions into graphite from ether electrolytes was recently discovered to be a surprisingly reversible process. The mechanisms of this "cointercalation reaction" are poorly understood and commonly accepted design criteria for graphite intercalation electrodes do not seem to apply. The excellent reversibility despite the large volume expansion, the small polarization and the puzzling role of the solid electrolyte interphase (SEI) are particularly striking. Here, in situ electrochemical dilatometry, online electrochemical mass spectrometry (OEMS), a variety of other methods among scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X‐ray diffraction (XRD) as well as theory to advance the understanding of this peculiar electrode reaction are used. The electrode periodically "breathes" by about 70–100% during cycling yet excellent reversibility is maintained. This is because the graphite particles exfoliate to crystalline platelets but do not delaminate. The speed at which the electrode breathes strongly depends on the state of discharge/charge. Below 0.5 V versus Na + /Na, the reaction behaves more pseudocapacitive than Faradaic. Despite the large volume changes, OEMS gas analysis shows that electrolyte decomposition is largely restricted to the first cycle only. Combined with TEM analysis and the electrochemical results, this suggests that the reaction is likely the first example of a SEI‐free graphite anode. Abstract : The reversible intercalation of solvated rather than naked ions into graphite is a peculiar electrode reaction that is currently studied for sodium‐ion batteries. Charging/discharging is accompanied by a large yet reversible electrode breathing and the charge transfer seems to occur over a kinetically stabilized interface without a solid electrolyte interphase.